STRATEGI KOMUNIKASI ECPAT INDONESIA UNTUK MEMERANGI PARIWISATA SEKS ANAK (PSA) - Dany .; Anggun Putri Dewanggi (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2018)
This study aims to find out and analyze “ECPAT’s Communication Strategies In Establishing Partnerships With The Private Sector In The National Tourism Industry To Combat Child Sex Tourism”. The problem formulation in this research is how ECPAT’s communication strategies in establishing partnerships with the private sector in the national tourism industry to combat child sex tourism. The research method that used in this research is descriptive qualitative approaching method. Data collection were obtained through in-depth interviews with program manager of ECPAT Indonesia, also as non-participant observator in the secretariat of ECPAT Indonesia and by collecting of documentary data that supported the research. The theory that used in this research is Advocacy Communication model from the Hopkins University for Communication Programs (CCP), USA. The research result showed that ECPAT Indonesia collaborated with several partners, including PHRI (Persatuan Hotel Indonesia), ASPPI (Asosiasi Pelaku Pariwisata Indonesia), Taxi Putra as transportation services, PT Angkasa Pura II and Accor Group Hotel. The collaboration was built using Advocacy Communication model from the John Hopkin, especially in mobilization and action stages, by forming the “ Down To Zero” program with coalition partners.